MANAJEMEN KELAS PADA PEMBELAJARAN AKIDAH AKHLAK UNTUK MENINGKATKAN PRESTASI SISWA DENGAN METODE THINK PAIR SHARE - imas sitinurohmah (ASWAJA: Jurnal Pendidikan dan Keislaman, 2021)
The government strives to improve the quality of education continuously by using various learning methods. This is done so that the purpose of education in the Republic of Indonesia Law no. 20 of 2003 can be achieved. However, the facts in the field of Active, Innovative, Creative, Effective and Fun learning are still not implemented. The indicator during discussion activities is that not all students are active so that the learning objectives are not entirely focused on learning morals which have an impact on student achievement. A step is needed to overcome these problems by using classroom management and strengthening the Think Pair Share (TPS) learning method. Class management is classroom governance while the Think Pair Share (TPS) method is how to learn to share, pair and present. The purpose of this study is to determine the planning, implementation, evaluation, learning outcomes and supporting factors, barriers and solutions. The author describes classroom management, learning morals, learning achievement and the TPS method to make it easier to describe research in the literature review. The research method used is descriptive qualitative analysis by collecting data through observation, interviews and documentation. The research process is determined by the subject, approach, type, location and research technique as well as testing the validity of the data and data analysis. The results of this study are classroom management carried out by PAI teachers, namely preparing learning programs according to the Think Pair Share (TPS) method, carrying out learning by using paired discussions and presenting the results of discussions and evaluating learning by evaluating process, output, formative and summative. The conclusion of this study is that the Think Pair Share (TPS) method is able to improve student achievement with indicators of cognitive, affective and psychomotor values ??exceeding the KKM standard.